UJI BEBERAPA CAMPURAN PUPUK ORGANIK CAIR SAMPAH PASAR DENGAN AIR TERHADAP BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Damanik, Fandy P; ', Sampoerno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the effect of mixture of organic liquid fertilizer of market waste with water and get the best mixture on growth of oil palm seeds in main nursery. Research was conducted at the experimental farm of Agriculture Faculty, University of Riau from March to July 2014. This research arranged experimentally using Completely Randomized Design (CRD), consist of 6 treatments with 4 replication so obtained 24 units of experiment. The treatment were: without organic liquid fertilizer, 1 liter of organic liquid fertilizer + 9 liters of water, 1 liter of organic liquid fertilizer + 14 liters of water, 1 liter of organic liquid fertilizer + 19 liters of water, 1 liter of organic liquid fertilizer + 24 liters of water, 1 liter of organic liquid fertilizer + 29 liters of water. Parameters observed were the increase of seeds height, increase of leaves number, increase of hump diameter, root volume, root crown ratio and dry seeds weight. Data were analyzed using analysis of variance (ANOVA) followed by Duncan's test at 5% level. The results showed that treatment mixture of organic liquid fertilizer of market waste with water affects on increase of seeds height, increase of hump diameter, increase of leaves number, root volume and dry seeds weight, but not affect on root crown ratio. A mixture of 1 liter of organic liquid fertilizer of market waste + 29 liters of water gave better effect than other treatments on all observed parameters. Keywords: organic liquid fertilizer of market waste, oil palm, main nursery.